Lingvistik, systemdigtning og Grundtvig - Toftdahl, Hellmut (Grundtvig-studier, 1971)
Linguistics, systemic poetry and Grundtvig By Hellmuth Toftdahl In this brief essay Grundvig5s poetics is juxtaposed with the view of poetry that, in Denmark, has been put forward by, among others, the poet and critic Per Højholt and supported by Niels Egebak. The following points are argued against:1. The assumption that any linguistic expression that is shaped along traditional lines determined by communication is lifeless and distant and leaves the listener or reader unaffected.2. The assumption that any linguistic expression gains life and becomes exciting only when, somehow or other, it breaks down the conventions surrounding the process of communication.From this it is concluded:1. By absorbing the blocks of linguistic material with which he is faced, the reader does not experience a finished work of art, but has to produce the work for himself2. The linguistic act becomes revolutionary in so far as the linguistic universe of the reader is undermined from within by the poison that has been smuggled in with the linguistically revolutionary text. An unprejudiced attitude is indoctrinated without arguments, but by causing the reader’s linguistic universe to disintegrate, without giving him a chance to defend himself. The poet forces the crisis of identity upon the reader.The young Grundtvig’s thoughts supply an interesting alternative or supplement to the view of literature that has been outlined above. To him poetry was not only a means of communication, it also possessed a magical power that might be transmitted to the receiver, counteracting his tendency to stagnation, and giving him the powers of expressing himself. According to Grundtvig, poetry originated in a vision, i. e. a spontaneous experience of universal rationality. To the individual this experience appears absurd only if he is over-occupied with his own brief history. A sound human being is convinced that reason exists, but that it is a waste of energy to brood over its nature. Time will show what truth is.To Grundtvig all ideologies were pitiful attempts to make a substitute for religion. True poetry frees man from the fetters that he has imposed upon himself, and gives rise to a feeling of freedom, of participation in an outer, organic reality.